The Effects Of Students’ Lexical Knowledge Of Collocation And Grammar Mastery Towards Students’ Reading Comprehension - Eva Yuni Rahmawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
The objective of this research was to determine and to investigate the effect of lexical knowledge of collocation towards student’s reading comprehension, the effect of grammar mastery towards student’s reading comprehension, and the effects of lexical knowledge of collocation grammar mastery altogether towards students’ reading comprehension. The method which used is a survey method. Sample was taken as many as 60 students with simple random technique. Data collected by test directly to the sample. Data analysis using descriptive statistics such finding mean, median, mode, standard deviation, and inferential statistics is to look for multiple regression by using ANOVA and coefficient table. This research was conducted from September to December. The results of this research explained that: 1) there are significant effects of lexical knowledge of collocation and grammar mastery altogether towards students’ reading comprehension skill. The result has shown Ftest = 3.665 > Ftable = 3.15 and Sig = 0.032 < 0.05, 2) there is a significant effect of lexical knowledge of collocation towards students reading comprehension skill. The result has shown the score of Sig = 0.043 < 0.05 and ttest = 2.068 while ttable = 1.64 ttest > ttable, 3) there is a significant effect of grammar mastery towards students’ reading comprehension skill. The result has shown the score of Sig = 0.044 < 0.05 and ttest = 2.056 while ttable = 1.64 ttest > ttable.Key Words : Lexical Collocation, Grammar Mastery, Reading Comprehension